Evaluation of in vivo bioactivities of recombinant hypo- (FSH21/18) and fully- (FSH24) glycosylated human FSH glycoforms in Fshb null mice. (5th December 2016) - Wang, Huizhen; May, Jacob; Butnev, Viktor; Shuai, Bin; May, Jeffrey V.; Bousfield, George R.; Kumar, T. Rajendra
Abstract: The hormone - specific FSHβ subunit of the human FSH heterodimer consists of N-linked glycans at Asn 7 and Asn 24 residues that are co-translationally attached early during subunit biosynthesis. Differences in the number of N-glycans (none, one or two) on the human FSHβ subunit contribute to macroheterogeneity in the FSH heterodimer. The resulting FSH glycoforms are termed hypo-glycosylated (FSH 21/18, missing either an Asn 24 or Asn 7 N-glycan chain on the β - subunit, respectively) or fully glycosylated (FSH 24, possessing of both Asn 7 and Asn 24  N-linked glycans on the β - subunit) FSH. The recombinant versions of human FSH glycoforms (FSH 21/18 and FSH 24 ) have been purified and biochemically characterized. In vitro functional studies have indicated that FSH 21/18 exhibits faster FSH- receptor binding kinetics and is much more active than FSH 24 in every assay tested to date. However, the in vivo bioactivity of the hypo-glycosylated FSH glycoform has never been tested. Here, we evaluated the in vivo bioactivities of FSH glycoforms in Fshb null mice using a pharmacological rescue approach. In Fshb null female mice, both hypo- and fully-glycosylated FSH elicited an ovarian weight gain response by 48 h and induced ovarian genes in a dose- and time-dependent manner. Quantification by real time qPCR assays indicated that hypo-glycosylated FSH 21/18 was bioactive in vivo and induced FSH-responsive ovarian genes similar to fully-glycosylated FSH 24 . Western blot analyses followed by densitometry of key signaling components downstream of the FSH-receptor confirmed that the hypo-glycosylated FSH 21/18 elicited a response similar to that by fully-glycosylated FSH 24 in ovaries of Fshb null mice. When injected into Fshb null males, hypo-glycosylated FSH 21/18 was more active than the fully-glycosylated FSH 24 in inducing FSH-responsive genes and Sertoli cell proliferation. Thus, our data establish that recombinant hypo-glycosylated human FSH 21/18 glycoform elicits bioactivity in vivo similar to the fully-glycosylated FSH. Our studies may have clinical implications particularly in formulating FSH-based ovarian follicle induction protocols using a combination of different human FSH glycoforms. Highlights: In vivo bioactivity of recombinant hypo (FSH 21/18 ) - and fully (FSH 24 ) - glycosylated FSH was tested in Fshb −/- mice. Both the FSH glycoforms elicited an ovarian weight gain response and induced antrum formation in Fshb −/- female mice. In ovarian gene induction assays, FSH glycoforms were found active in the absence of endogenous FSH. Both the FSH glycoforms elicited a testis weight gain response in Fshb −/- male mice. In Sertoli cell proliferation and testis gene expression assays, FSH 21/18 glycoform was found more active than FSH 24 .